(untitled) (Future Cities and Environment, 2024)
The slum management model is also part of effective development efforts that need to be improved and developed in an integrated, directed, planned, and sustainable manner. The objectives of this study are; (1) To find out how the pattern of slum management in Kendari City, and (2) Providing a Collaborative Model for Sustainability of Slum Management. It was conducted using a qualitative descriptive approach with observation, naturalistic, and phenomenological methods to reveal phenomena that occur based on observations and information obtained in the field. The results of the study confirmed that the slum management strategy can only be implemented with a new approach, namely the paradigm of network optimization towards welfare. This paradigm does not only prioritize the infrastructure aspect which connotes the economy can realize prosperity independently. Effective slum management is to synergize all management resources in an institutionalized sustainable collaboration model. Slum management in applying a patterned network optimization approach in 3 (three) major parts; (1) management of access to intra-community resources, (2) management of network access to government organizations, and (3) Optimization of non-government network management, in a sustainable collaboration for slum management can be more effective.